The Influence of Rice Production on the Welfare of Rice Farmers in Perbaungan District, Serdang Berdagai Regency - Sihihab, Muhammad Wahyu; Gulo, Ahmad Jumadin; Ruslan, Dede; Sari, Raina Linda (Politeknik Negeri Bengkalis, 2024)
The agricultural sector is vital in most developing countries' economies, especially Indonesia. Economic development is carried out to improve community welfare. Improving farmers' welfare is one of the visions and missions of agricultural development in achieving food self-sufficiency and improving farmers' welfare. Deli Serdang Regency is one area with an excellent agrarian sector, especially rice farming. Even though the rice farming sector is still the primary sector in the economy of Deli Serdang Regency, there are still problems related to farmer welfare. Some issues include fluctuating grain prices and rice production, which must still be optimal. Besides that, climate change and a need for more understanding regarding the technical matters of managing rice plants and equipment must be improved, impacting rice farmers' productivity. This research aims to determine the factors of rice production, grain prices, capital, Labor, consumption, land area, technology, and education relevant to improving rice farmers' welfare in Perbaungan District, Deli Serdang Regency. Data processing uses Multiple Linear Regression. Based on test results. The results of multiple linear regression testing show that simultaneous hypothesis testing of capital, land area, grain prices, and Labor together have a positive and significant effect on the welfare of farmers in the Perbaungan District.Keywords: Â Capital, Land Area, Labor, and Farmers' Welfare